Comparison of capping and mixing of calcined dolomite and zeolite for interrupting the release of nutrients from contaminated lake sediment - Alvarado, Jesteen Naldo; Hong, Seung Hee; Lee, Chang Gu; Park, Seong Jik (Environmental Science and Pollution Research, 2020)
This study aimed to assess the effectiveness of capping and mixing of calcined dolomite and zeolite for the remediation of sediment contaminated with nitrogen (N) and phosphorus (P). Laboratory incubation experiments were performed to monitor the release of NH4-N, NO3-N, T-N, PO4-P, and T-P from the sediment. pH, electric conductivity (EC), oxidation reduction potential (ORP), and dissolved oxygen (DO) in overlying water for 60 days were evaluated. Dolomite-amended sediment has high pH and EC. Zeolite and dolomite capping effectively interrupted the release of N and P, respectively; capping was found to be more effective than mixing. The mixture of dolomite and zeolite was also effective; however, their efficiencies were influenced by their placement. The remediation efficiencies when the dolomite was placed above the zeolite cap layer (DOL/ZEO_CAP) were 95.9%, 101.6%, and 100.2% for NH4-N, PO4-P, and total, and the total remediation efficiency of DOL/ZEO_CAP was twice that of the opposite placement (ZEO/DOL_CAP). Low remediation efficiencies for NH4-N and T-N were observed in ZEO/DOL_CAP because NH4 + adsorption on zeolite was hindered by Ca2+ and Mg2+ released from the dolomite. The combination of dolomite and zeolite can be used as a capping material for simultaneously interrupting the release of both nitrogen and phosphorus, but their placement should be considered.
Keywords: Calcium Carbonate; Geologic Sediments; Lakes; Magnesium; Nitrogen; Nutrients; Phosphorus; Water Pollutants, Chemical; Zeolites; Capping; Dolomite; Mixing; Nutrient; Placement; Sediment; Zeolite